Therapeutic approach towards Amlapitta in Bhaishajya Ratnavali - Sharma, Shivani; Sharma, Reetu; Godatwar, Pawankumar (International Research Journal of Ayurveda & Yoga, 2021)
Modern day lifestyle is associated with many health-related issues and Amlapitta is one of them. Amlapitta is a disease caused due to imbalance of Pitta Dosha which needs attention in early stage to prevent further complications. Ayurveda has been successfully treating this condition since thousands of years. Bhaishajya Ratnavali is one of the texts of Ayurveda which prescribes medications for various diseases. Amlapitta has been described in a separate chapter in Bhaishajya Ratnavali. It consists both herbal and herbo-mineral formulations for its treatment. This article reviews the treatment of Amlapitta as mentioned in Bhaishajya Ratnavali and attempts to explain the probable mode of action of the formulations.